2019
DOI: 10.4047/jkap.2019.57.3.263
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive esthetic treatment of isolated microdontia using new high-translucent cubic-phase zirconia (5Y-PSZ) laminate veneers: A case report

Abstract: Current trends in restorative dentistry focus on improving the esthetics and keeping the sound dental tissues as long as possible. The aims of this case report were to describe the successful outcome of cubic-phase zirconia laminate veneers for a patient with isolated microdontia by using a digital workflow, and to describe their clinical implications. A 15-year-old female who had isolated microdontia in combination with spacing visited Ajou University Dental Hospital for esthetic treatment. In this case, 6 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This agrees with Ozel and Aykor's study, in which it was found that there was no marginal discoloration of lithium disilicate crystal (e.max) veneers (Nejatidanesh et al, 2018 ). In addition, it agrees with Ahn et al ( 2019 ) who observed six anterior veneers for 6 months, and no deboning or staining was observed (Ahn et al, 2019 ). Contrastively, this study disagreed with Aslan's long‐term study, which traced 11.7% of marginal discoloration in lithium disilicate glass‐ceramic veneers (Aslan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with Ozel and Aykor's study, in which it was found that there was no marginal discoloration of lithium disilicate crystal (e.max) veneers (Nejatidanesh et al, 2018 ). In addition, it agrees with Ahn et al ( 2019 ) who observed six anterior veneers for 6 months, and no deboning or staining was observed (Ahn et al, 2019 ). Contrastively, this study disagreed with Aslan's long‐term study, which traced 11.7% of marginal discoloration in lithium disilicate glass‐ceramic veneers (Aslan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…(2019) who observed six anterior veneers for 6 months, and no deboning or staining was observed (Ahn et al, 2019). Contrastively, this study disagreed with Aslan's long-term study, which traced 11.7% of marginal discoloration in lithium disilicate glass-ceramic veneers (Aslan et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…38 The 5 mol% cubic phase zirconia is found to be more resistant to aging behavior than 3 mol% yttria-stabilized tetragonal zirconia (3Y-TZP). 44,45 5Y-PSZ can offers ultra-translucency that is similar or even higher than that of (LS2) ceramic. 44,46,47 Other studies have reported that lithium disilicate has higher levels of translucency than that of cubic-phase zirconia.…”
Section: Discussionmentioning
confidence: 94%
“…44,45 5Y-PSZ can offers ultra-translucency that is similar or even higher than that of (LS2) ceramic. 44,46,47 Other studies have reported that lithium disilicate has higher levels of translucency than that of cubic-phase zirconia. 44 Unfortunately, 5Y-PSZ lost a part of its toughening mechanism when acquiring translucency.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation